2013
DOI: 10.1136/annrheumdis-2012-202347
|View full text |Cite
|
Sign up to set email alerts
|

The role of methotrexate co-medication in TNF-inhibitor treatment in patients with psoriatic arthritis: results from 440 patients included in the NOR-DMARD study

Abstract: We found similar responses to TNFi in patients with and without concomitant MTX, but drug survival was superior in patients receiving co-medication. The effect of MTX on drug survival was most prominent in patients receiving IFX. Smoking at baseline and use of TNFi as monotherapy were identified as independent predictors of drug discontinuation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
132
4
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(162 citation statements)
references
References 22 publications
(27 reference statements)
17
132
4
9
Order By: Relevance
“…Although not strongly supported by the evidence thus far and not proposed for the treatment of axial disease by ASAS/EULAR recommendations 19 , a favorable effect of MTX, especially for those with peripheral arthritis, cannot be excluded. Concerning PsA, we and others have found a favorable effect of MTX co-administration 15,20 , while a report from the COnsortium of Rheumatology Researchers Of North America US-based registry found no effect 21 . A systematic literature review showed that the use of MTX prolongs TNFi 23,24 .…”
Section: Rheumatologymentioning
confidence: 59%
“…Although not strongly supported by the evidence thus far and not proposed for the treatment of axial disease by ASAS/EULAR recommendations 19 , a favorable effect of MTX, especially for those with peripheral arthritis, cannot be excluded. Concerning PsA, we and others have found a favorable effect of MTX co-administration 15,20 , while a report from the COnsortium of Rheumatology Researchers Of North America US-based registry found no effect 21 . A systematic literature review showed that the use of MTX prolongs TNFi 23,24 .…”
Section: Rheumatologymentioning
confidence: 59%
“…However, the influence of MTX in combination with TNF inhibitors has not been well studied in PsA 4 . A study based on observational data from Norway did not detect a difference in clinical responses with the concomitant use of MTX and TNF inhibitors, but the authors stressed that they did not have the data to address the issue of peripheral versus axial disease, a major potential confounding factor 8 .…”
Section: Discussionmentioning
confidence: 99%
“…To further analyze drug tolerability, we examined withdrawal rates during the 24 months of therapy. Other studies in patients with PsA have found that MTX increases the rate of persistence with anti-TNF therapy 6,7,8 and that PsA patients treated with ADA plus MTX have higher serum concentrations of ADA than those treated with ADA alone 16,17 , possibly due to suppression of development of anti-ADA antibody. However, our findings do not support an increased rate of treatment persistence with ADA in patients receiving concomitant MTX.…”
Section: Rheumatologymentioning
confidence: 94%
See 1 more Smart Citation
“…This has been studied in the Norwegian, Swedish, and CORRONA PsA registries in relation to etanercept (ETN), ADA, and IFX 14,15,16 . IFX survival is more prolonged when MTX is combined compared to IFX monotherapy.…”
mentioning
confidence: 99%